The creation of innovative tourism products via local actor analysis and their organization in the territory - LAMYA MAGHNAOUI (Journal of Advanced Research in Social Sciences and Humanities, 2020)
Aim: This study’s overarching goal is to establish a theoretical foundation for reflection on Geo-tourism and its approach by assigning monetary values to territorial resources.Method: We took a qualitative approach by reading up on related works, fads in the field, and prevailing tenets in the academic canon.Findings: Tourism is one of the world’s fastest-growing economic sectors, thanks to decades of consistent growth and a greater diversity of offerings. Indeed, in recent years, geological tourism has emerged as an alternative that can be associated with classical tourism. This type of tourism involves the presentation of a territory’s geological and geomorphological heritage and draws attention to the region’s enormous geological and cultural diversity.Implications/Novel Contribution: Our research contributes to an ongoing territorial project to organize these areas (what can be done? To what effect? Sales, functions). The transboundary and interregional nature of geological tourism is made possible through the exploitation, mobilization, and combination of these resources.